Body Mass, Physical Activity and Eating Habits Changes during the First COVID-19 Pandemic Lockdown in Poland - Dobrowolski, Hubert (Int J Environ Res Public Health, 2021)
The outbreak of the COVID-19 pandemic caused a number of changes in social life around the world. In response to the growing number of infections, some countries have introduced restrictions that may have resulted in the change of the lifestyle. The aim of our study was to investigate the impact of the lockdown on body weight, physical activity and some eating habits of the society. The survey involving 183 people was conducted using a proprietary questionnaire. The mean age of the study participants was 33 ± 11 and mean height 169 ± 8 cm. An average increase in body weight was observed in 49.18% by 0.63 ± 3.7 kg which was the result of a decrease in physical activity and an increase in food consumption. We also observed a decrease in PAL from 1.64 ± 0.15 to 1.58 ± 0.13 and changes in the amount of food and individual groups of products consumption, including alcohol. Among the study participants who did not lose body mass, there was an average weight gain of 2.25 ± 2.5 kg. In conclusion, an increase of weight was shown in about half of the respondents in the study group which was associated with a decrease in physical activity and an increase in the consumption of total food and high energy density products.